2018
DOI: 10.1007/s12192-018-0904-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of DJ-1 (encoded by the human PARK7 gene) protects neuronal cells from sevoflurane-induced neurotoxicity

Abstract: Sevoflurane, an inhaled ether general anesthetic agent, exerts a variety of neurotoxic effects, including oxidative stress, mitochondrial dysfunction, and neuronal apoptosis. However, the underlying molecular mechanisms remain to be elucidated. DJ-1 is a protein that exerts neuroprotective effects against different kinds of stress through multiple pathways. This study aimed to investigate the neuroprotective effects of DJ-1 against sevoflurane-induced neurotoxicity. Here, we found that sevoflurane treatment si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Beyond the small gene categories from above, we also found several other interesting genes. The PARK7 gene, a gene that codes for a protein that protects from oxidative stress[ 64 ], does not appear in a pig related context in the literature, but it is found in a known FCR QTL region, and its eQTL SNP was found in a module highly correlated to FE in our previous work [ 47 ]. MFF was similarly found in a known FCR QTL region.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the small gene categories from above, we also found several other interesting genes. The PARK7 gene, a gene that codes for a protein that protects from oxidative stress[ 64 ], does not appear in a pig related context in the literature, but it is found in a known FCR QTL region, and its eQTL SNP was found in a module highly correlated to FE in our previous work [ 47 ]. MFF was similarly found in a known FCR QTL region.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Moreover, an in vitro study demonstrated that inhalation of sevoflurane could increase β-AP levels and induce caspase activation and apoptosis, which can ultimately facilitate the progression of Alzheimer's disease. Studies showed that sevoflurane anaesthesia could reduce the rate of neurogenesis and decrease neuronal survival in the hippocampus, causing neurotoxicity and cognitive impairment in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that sevoflurane anaesthesia could reduce the rate of neurogenesis and decrease neuronal survival in the hippocampus, causing neurotoxicity and cognitive impairment in aged rats. 37,38 Moreover, an in vitro study demonstrated that inhalation of sevoflurane could increase β-AP levels and induce caspase activation and apoptosis, which can ultimately facilitate the progression of Alzheimer's disease. 39 Additionally, it is also revealed that exposure sevoflurane in aged rats led to learning and memory deficits through endoplasmic reticulum stress (ERS)-induced apoptosis of the neurons.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Sevoflurane, an inhalational anaesthetic, has been identified to mediate multiple processes including oxidative stress, mitochondrial damage and neuronal apoptosis. 5 It has been reported that the action of SEV in myocardial I/R injury is mediated by microRNA-135b-5p. 6 This suggests that SEV may regulate other microRNAs (miRNAs) as molecular mechanisms underlying its effects against myocardial I/R injury.…”
Section: Introductionmentioning
confidence: 99%